2006
DOI: 10.1121/1.2166611
|View full text |Cite
|
Sign up to set email alerts
|

The use of visual cues in the perception of non-native consonant contrasts

Abstract: This study assessed the extent to which second-language learners are sensitive to phonetic information contained in visual cues when identifying a non-native phonemic contrast. In experiment 1, Spanish and Japanese learners of English were tested on their perception of a labial/ labiodental consonant contrast in audio (A), visual (V), and audio-visual (AV) modalities. Spanish students showed better performance overall, and much greater sensitivity to visual cues than Japanese students. Both learner groups achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 36 publications
11
78
1
4
Order By: Relevance
“…In fact, this is precisely the situation encountered when attempting to understand the sounds of a second language. In line with this idea, behavioural studies have shown that the addition of visual information (e.g., mouth movements) can enable the phonological discrimination between non-native sounds, which are otherwise undistinguishable on the basis of auditory cues alone Reisberg et al, 1987;Hirata and Kelly, 2010), resulting in an improved overall comprehension of L2 (although the contribution of AV integration in L2 perception is not always effective; Hazan et al, 2006). For example, a recent study showed that available visual mouth movements improve auditory L2 learning (Hirata and Kelly, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…In fact, this is precisely the situation encountered when attempting to understand the sounds of a second language. In line with this idea, behavioural studies have shown that the addition of visual information (e.g., mouth movements) can enable the phonological discrimination between non-native sounds, which are otherwise undistinguishable on the basis of auditory cues alone Reisberg et al, 1987;Hirata and Kelly, 2010), resulting in an improved overall comprehension of L2 (although the contribution of AV integration in L2 perception is not always effective; Hazan et al, 2006). For example, a recent study showed that available visual mouth movements improve auditory L2 learning (Hirata and Kelly, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…It has been argued that since Mandarin is a tone language, L1-Mandarin speakers rely more on tones than on visual cues in speech perception (Sekiyama, 1997;Sekiyama and Tohkura, 1993). Moreover, Hazan et al (2006) indicated that L2 listeners may lose sensitivity to visemes that do not exist in their L1. These predictions would be confirmed if we look at the results in the pre-test, in which the subjects' accuracy in the perception of the target contrasts was pretty low.…”
Section: The Effect Of Articulatory Information On the Subjects' Percmentioning
confidence: 99%
“…Hazan et al (2006) identified three types of visual speech categories according to their occurrence in language learners' L1 and L2: (1) a visual category that exists in both the L1 and L2; (2) a visual category that occurs in the L2 but not the L1; (3) a visual category that occurs in both the L1 and the L2, but is used in different phonetic distinctions in the L1 and the L2 (Wang et al, 2009). Hazan et al, (2006) predict that due to the influence of L1 experience, L2 learners may lose sensitivity to visual categories which do not exist in their L1. Consequently, they may find difficulty for their perception of these speech sounds, specifically in terms of being unable to associate these sounds with their corresponding visual categories.…”
Section: Factors Affecting L2 Speech Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…No centro do debate está a questão do quanto a produção dos sons da L2 é precedida pela percepção dos mesmos, ou se a percepção é apenas uma dos elementos que contribuem para a produção dos sons da L2. Dentre esses outros elementos estão a utilização de informações visuais, obtidas quando o aprendiz de L2 observa os movimentos articulatórios de um falante da língua-alvo (HAZAN; SENNEMA; FAULKNER et al, 2006;KLUGE, 2010), bem como o uso de informações sobre as correpondências grafofono-fonológicas na L2 (BASSETTI, 2009;ZIMMER;ALVES, 2009).…”
Section: Introductionunclassified